2013
DOI: 10.1089/sur.2012.158
|View full text |Cite
|
Sign up to set email alerts
|

Intracolonic Vancomycin for Severe Clostridium difficile Colitis

Abstract: Background: Clostridium difficile colitis is associated with increased age, antibiotic usage, and hospitalization. Severe C. difficile colitis refractory to medical therapy may require surgical intervention including subtotal colectomy. We initiated an adjuvant intracolonic vancomycin (ICV) enema protocol for inpatients with severe C. difficile colitis and compared the response to this therapy in patients from the community and nursing homes. Methods: A single-hospital, retrospective chart review was done on 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 39 publications
1
18
0
2
Order By: Relevance
“…Kim et al showed that the majority of patients who were given intracolonic vancomycin had complete resolution of symptoms although subsequently, two developed severe recurrence with fatal outcome [6]. Among our patients, four were given intracolonic vancomycin in addition to standard therapy before initiation of teicoplanin, but this did not result in clinical cure.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Kim et al showed that the majority of patients who were given intracolonic vancomycin had complete resolution of symptoms although subsequently, two developed severe recurrence with fatal outcome [6]. Among our patients, four were given intracolonic vancomycin in addition to standard therapy before initiation of teicoplanin, but this did not result in clinical cure.…”
Section: Discussionmentioning
confidence: 66%
“…Another therapeutic option for severe refractory CDI is intracolonic delivery of vancomycin by rectal enema [6]. Kim et al showed that the majority of patients who were given intracolonic vancomycin had complete resolution of symptoms although subsequently, two developed severe recurrence with fatal outcome [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A single-center case series report of 47 patients with severe C. difficile colitis with surgical consultation recommended initiation of an adjuvant intracolonic vancomycin enema (1 g/500 mL normal saline every 6 h) protocol and 70% of patients responded with complete resolution without need for surgery. Multivariable logistic regression confirmed that acidosis and hypoalbuminemia were significantly associated with incomplete response to intracolonic vancomycin enema treatment [79].…”
Section: Timing Of Surgical Consultationmentioning
confidence: 69%
“…27 In cases of extremely severe C. difficile colitis, intracolonic vancomycin administration may have the potential to be used as an adjunct, to ensure higher concentrations of the drug in the colon. 32,33 This may involve the use of an intracolonic bolus with an intravenous solution of vancomycin. A rectal retention enema such as 500 mg of vancomycin in 1 L of saline solution may be another option.…”
Section: Alternative Vancomycin Dosing Strategiesmentioning
confidence: 99%